PELAKSANAAN AKUNTABILITAS PELAYANAN PUBLIK DALAM PENGURUSAN KARTU KELUARGA (KK) DI KECAMATAN METRO SELATAN (STUDI PADA DESA SUMBERSARI KECAMATAN METRO SELATAN) - Mirnawati Mirnawati (Derivatif : Jurnal Manajemen, 2018)
The People complain about the length of bureaucracy that must be passed, ie starting from the level of RT, village head, District to the Department of Population and Civil Registry. In making Birth Certificate. They must change the Family Card to be taken care of starting from neighborhood level (RT), Sub-district, Sub-district to Population and Civil Registry.Family Card (KK) in Metro South District? The objective to be achieved is to know the implementation of accountability of Family Card Making Service in South Metro Sub-district Based on the description of the background that has been stated above, then the problem is formulated: How is the accountability implementation of KK-making service in Sumbersari Metro Selatan.In this research data collection method used interview, observation and documentation. Data analysis technique used is qualitative technique.